Penerapan Konseling Kelompok dengan Teknik Role Playing dalam Mengurangi Abusive Language pada Anak Usia Sekolah Dasar di Desa Seribandung - Lutfia Auliatinnisa; Kusnadi Kusnadi (Journal of Society Counseling, 2025)
This research is titled "The Application of Group Counseling with Role Playing Techniques in Reducing Abusive Language in Elementary School Children." The study aims to analyze the use of abusive language among elementary school children, which is a common issue in their social development and can interfere with interpersonal relationships. The use of abusive language is often caused by the children's inability to manage their emotions and express their feelings in more positive ways. Therefore, role-playing techniques were chosen as a method to help children practice better social skills and develop empathy towards others. This research uses a qualitative approach with five child subjects selected based on the abusive language problems they faced. Data was collected through interviews with the children, teachers, and social community, direct observation during group counseling sessions, and documentation of the children's development over four counseling sessions. The results of the study show that the implementation of group counseling with role-playing techniques is effective in reducing the use of abusive language among children. Children who previously often used abusive words in social interactions began to show improvements in emotional regulation and chose more polite words when facing situations that triggered frustration or anger. Furthermore, through role-playing sessions, children practiced more constructive ways to resolve conflicts with peers or teachers without using hurtful language. An increase in empathy was also observed, with children becoming more aware of the negative impact of abusive language on others' feelings and making efforts to improve their social relationships. Overall, role-playing techniques have been shown to help children replace harsh emotional expressions with more effective communication and build healthier social relationships.